A Gradient pH‐Sensitive Polymer‐Based Antiviral Strategy via Viroporin‐Induced Membrane Acidification. Issue 18 (9th March 2022) - Sun, Yizhe; Gong, Lidong; Yin, Yue; Zhang, Lei; Sun, Qiangming; Feng, Kai; Cui, Yimin; Zhang, Qiang; Zhang, Xuehui; Deng, Xuliang; You, Fuping; Lu, Dan; et al.
Abstract: Lipid‐membrane‐targeting strategies hold great promise to develop broad‐spectrum antivirals. However, it remains a big challenge to identify novel membrane‐based targets of viruses and virus‐infected cells for development of precision targeted approaches. Here, it is discovered that viroporins, viral‐encoded ion channels, which have been reported to mediate release of hydrogen ions, trigger membrane acidification of virus‐infected cells. Through development of a fine‐scale library of gradient pH‐sensitive (GPS) polymeric nanoprobes, the cellular membrane pH transitions are measured from pH 6.8–7.1 (uninfection) to pH 6.5–6.8 (virus‐infection). In response to the subtle pH alterations, the GPS polymer with sharp response at pH 6.8 (GPS6.8 ) selectively binds to virus‐infected cell membranes or the viral envelope, and even completely disrupts the viral envelope. Accordingly, GPS6.8 treatment exerts suppressive effects on a wide variety of viruses including SARS‐CoV‐2 through triggering viral‐envelope lysis rather than affecting immune pathway or viability of host cells. Murine viral‐infection models exhibit that supplementation of GPS6.8 decreases viral titers and ameliorates inflammatory damage. Thus, the gradient pH‐sensitive nanotechnology offers a promising strategy for accurate detection of biological pH environments and robust interference with viruses. Abstract : It is challenging to develop potent and broad‐spectrum antivirals. Gradient pH‐sensitive polymeric nanoprobes are designed for accurate measurement of the cellular membrane acidification induced by virus infection. In response to acidified membranes, one of the polymers selectively targets to virus‐infected cells and viruses, eventually lysing viral envelopes and exerting powerful activities against a variety of viruses.